Mentoring and coaching a lifeline for teachers in a multicultural setting - Gudwin, Denise M.; Salazar-Wallace, Magda D.; Sage eBooks (Thousand Oaks, Calif. : Corwin ; London : SAGE, 2010)
Filled with reproducable resources and real-life vignettes, this book focuses on coaching new teachers in culturally and linguistically diverse school settings, but can also be used in any setting.
Includes bibliographical references and index.
Specialized.
Description based on print version record.
Keywords: Multicultural education -- United States; Education, Bilingual -- United States; Teachers -- Training of -- United States; Mentoring -- United States; Personal coaching -- United States; Peer review -- United States; Electronic books